IMPLEMENTASI KURIKULUM 2013 MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI KOTA BUKITTINGGI - Abdurahman, Finda Afriani, Atmazaki, (Universitas Negeri Padang, 2017)
This article aims to describe the achievement level of making plan, implementation, and achievement in the assessmentlearning of Bahasa Indonesia on the implementation of curriculum 2013 at SMP N 2, SMP N 3, and SMP N 4 Bukittinggi. The research type was a qualitative research and quantitative research that used descriptive method. The techniques used in this research were observation, interview, and documentary research. The techniques used in analyzing the data were identification, presentation, and drawing conclusions. The result of the research found that whole aspects of planning, implementation, and assessmentlearning have been created as well by the Indonesian teachers of SMP N Bukittinggi based on the curriculum 2013 with good category.Kata kunci: Implementasi, kurikulum 2013, dan Bahasa Indonesia